Development of a microbial bioprocess for enzymatic breakdown of Ecklonia maxima using isolated microorganisms - Noach, Matthew Nigel (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.